Effect of Nanosized NiF2 Addition on the Transport Critical Current Density of Ag-Sheathed (Bi1.6Pb0.4)Sr2Ca2Cu3O10 Superconductor Tapes - M. Hafiz; R. Abd-Shukor (Advances in Materials Science and Engineering)
We report the effect of NiF2 (10 nm) additions on the transport critical current density, Jc of (Bi1.6Pb0.4)Sr2Ca2Cu3O10/Ag sheathed superconductor tapes. Pellets of (Bi1.6Pb0.4)Sr2Ca2Cu3O10(NiF2)x (x=0–0.05 wt.%) superconductor were prepared using the acetate coprecipitation method. The sample with 0.04 wt.% addition of NiF2 exhibited the highest Jc. Ag-sheathed (Bi1.6Pb0.4)Sr2Ca2Cu3O10(NiF2)0.04 superconductor tapes were fabricated using the powder-in-tube (PIT) method and sintered at 845°C for 50 and 100 h. Jc of nonadded tapes at 30 K sintered for 50 and 100 h was 6370 and 8280 A/cm2, respectively. Jc of (Bi1.6Pb0.4)Sr2Ca2Cu3O10(NiF2)0.04/Ag tape at 30 K sintered for 50 and 100 h was 14390 and 17270 A/cm2, respectively. In magnetic fields (0 to 0.7 T), Jc of the NiF2 added tapes was also higher compared with the nonadded tape indicating that NiF2 nanoparticles can act as effective flux pinning centers and longer sintering time improved the microstructure. A steeper increase in Jc was observed below 60 K in the NiF2 added tapes which coincided with the Neel temperature, TN of nanosized NiF2 (60 K). The pronounced enhancement of Jc was attributed to the strong interaction between flux line network and the antiferromagnetic NiF2 below TN.